Growth and yield response of Moringa oleifera (Lam) to different rates, method and timing of compost application. (2013)
Moringa oleifera (L) production is recently being advocated for its outstanding phytochemical components with high medicinal values. However, its production is being threatened with poor soil fertility most especially in urban areas. Field experiment was carried out to determine the effects of time, rate and method of compost application on the growth and yield of Moringa oleifera. Composts made from Mexican sunflower and poultry manure, applied at 2.5t/ha (CI) and 5.0t/ha (C2), with two methods of application (surface; MI and drilling: M2) and applied at different times of application (2 weeks before transplanting: T1 and 2 weeks after transplanting: T2) to give nine treatments (CIMITI, C2MITI, CIMITI, C2M2TI, CIMIT2, C2MIT2, CIM2T2, C2M2T2 and Control). The treatments were arranged using Randomized Complete Blocks Design (RCBD) and replicated three times. Data were collected on vegetative development such as number of leaves, number of branches, stem diameter and plant height formightly for 12 weeks beginning from four weeks after transplanting (4WAT). At 12 weeks, the plants were uprooted and separated into roots, stems and leaves for fresh and dry weights determination. The post-cropping soil analysis was also carried out following standard procedure. Results indicated that compost treatments significantly enhanced growth parameters (P ≤0.05). C2M2T2 was superior to other compost treatments. It gave the highest number of leaves, number of branches. stem diameter and plant height. Fresh weight and dry matter accumulation were also influenced by organic amendment compared to control, Soil analysis result showed that amendment with compost generally increased soil nitrogen, available phosphorus, and organic carbon content of the soil. It could be concluded that 5t/ha of compost, applied after transplanting using drilling method increased the cumulative yield of Moringa oleifera.